The Role of Wattpad in Vocabulary Development: A Narrative Inquiry - Rogas, Yasin Ali; Ristati; Pratika, Dellis (General English Education, 2026)
This study explores the role of Wattpad as a digital reading platform in supporting vocabulary development among Indonesian EFL learners. The research was motivated by the persistent issue of low reading motivation and limited vocabulary growth among students, despite increasing exposure to English through digital media. Using a qualitative descriptive design, data were collected through a semi-structured in-depth interview with one purposively selected participant who had actively read English stories on Wattpad. Findings revealed that the participant’s engagement with Wattpad contributed to the formation of consistent reading habits, driven by both social influence and intrinsic motivation. Wattpad provided authentic, contextualized exposure to English vocabulary, allowing the participant to acquire and apply new words naturally in both academic and personal communication. Furthermore, the platform fostered pragmatic awareness and confidence in using English expressively and appropriately. Despite challenges such as misinterpretation and inconsistent language quality, the participant demonstrated autonomy and critical literacy in overcoming them. Overall, the study highlights Wattpad’s pedagogical potential as an informal yet effective digital environment that promotes self-directed vocabulary learning and enhances reading motivation. The findings offer valuable implications for integrating authentic digital reading materials into EFL instruction to foster meaningful and learner-centered language development.